2016
DOI: 10.1111/ene.12946
|View full text |Cite
|
Sign up to set email alerts
|

Migraine in patients with systemic lupus erythematosus is associated with reduced cerebral grey matter volume but not with measures of glial activation or anti‐NR2 or anti‐P antibodies

Abstract: Systemic lupus erythematosus patients with migraine have a diffuse reduction in GM compared to patients without migraine. This finding was not observed in healthy subjects with migraine, and selected biomarkers did not indicate specific pathophysiological processes in the brain. These findings indicate that unknown pathogenic processes are responsible for the increased frequency of migraine in SLE patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
(33 reference statements)
0
7
0
Order By: Relevance
“…Neuroimaging studies based on MRI [ 184 , 185 ], H1-Magnetic resonance spectroscopy [ 186 ] and single-photon emission computed tomography [ 187 , 188 ] have been also performed in order to identify the anatomic and functional correlates underlying the possible association between SLE and headache. Unfortunately, these studies were not able to definitely clarify this issue due to the small sample size and in some cases the lack of a control group [ 188 ].…”
Section: Headache and Connectivitismentioning
confidence: 99%
“…Neuroimaging studies based on MRI [ 184 , 185 ], H1-Magnetic resonance spectroscopy [ 186 ] and single-photon emission computed tomography [ 187 , 188 ] have been also performed in order to identify the anatomic and functional correlates underlying the possible association between SLE and headache. Unfortunately, these studies were not able to definitely clarify this issue due to the small sample size and in some cases the lack of a control group [ 188 ].…”
Section: Headache and Connectivitismentioning
confidence: 99%
“…In total, 17 studies with data on anti-NR2A/B antibodies in 2,212 SLE patients, 99 patients with other autoimmune diseases (e.g., antiphospholipid syndrome, myasthenia gravis, and autoimmune polyendocrine syndrome I) and 538 healthy controls were included. Overall pooled prevalence of serum/plasma anti-NR2A/B antibodies was higher in SLE patients [24.6% (95% CI 18.5–32.0%)] compared to other autoimmune diseases [14.8% (95% CI 2.2-56.9)] and healthy controls [7.6% (95% CI 4.6–12.4%)] ( p = 0.001) (40). SLE patients with NP syndromes had more frequently NR2A/B antibodies [pooled OR = 1.607 (95% CI 1.041–2.479), p = 0.032] as compared to SLE without NP syndromes.…”
Section: Studies Applying Acr Criteriamentioning
confidence: 99%
“…Differential prevalence of migraine in SLE patients has been reported from various populations ranges from 6.82% to 66.09%. Furthermore, some studies reported a higher frequency of migraine in SLE patients compared to healthy controls, 9,[11][12][13][14]17,18,23 while others remained comparable. 8,10,15,16 The differential frequency of migraine in various populations and while comparing patients and controls may be attributed to smaller sample size, ethnicity of the enrolled patients or geographical location, and other confounding factors of migraine.…”
Section: Introductionmentioning
confidence: 95%